Impact of participative leadership and hierarchical organizational culture on performance in Oman's food processing industry - Maqbali, Rashid Al; Khudari, Mohamed (Edelweiss Applied Science and Technology, 2024)
This study investigates the complex interaction between organizational culture, employee engagement, leadership styles, and overall performance in Oman's Food Processing Sector, with a specific focus on the State-owned Oman Food Investment Holding Company (OFIC). A uniform questionnaire is distributed to 2,394 OFIC personnel across different divisions. Statistical analyses indicate that there are relationships at the organizational level. Specifically, participative leadership has a significant positive effect on performance (β = 0.144, p = 0.004). Additionally, a hierarchical corporate culture improves effectiveness (β = 0.555, p < 0.001) and also influences the connection between participative leadership and performance (β = -0.413, p < 0.001). Employee engagement does not play a role in moderating the relationship between participatory leadership and performance. The report highlights the importance of customized leadership and cultural strategies to maximize success in Oman's food business, with a focus on particular suggestions for improving organizations.